Research on Temperature Field Analysis Method of High-Speed Bearing Chamber–Bearing System - Ping Gong; Jingjing Zhang; Zhenxia Liu; Manyuan Li (Applied Sciences)
The analysis of the temperature field of a high-speed bearing chamber–bearing system is very complex. We used the temperature field analysis method on a 40,000 rpm bearing chamber–bearing system by simulation, which builds on the finite volume method and introduces a decoupling method that separates fluid dynamics from the thermal analysis of the solid temperature field. Firstly, according to bearing operating conditions, the characteristics of the oil–air two-phase distribution in the bearing chamber are determined using the Volume of Fluid (VOF) method. The convective heat transfer boundary conditions derived from this analysis serve as the thermal boundary conditions for the subsequent thermal analysis. Secondly, considering the heat generation of the bearings and the thermal boundary conditions, a temperature field analysis model is formulated. The calculated results are found to be in close agreement with the actual test data, with an error of less than 10% under three operational conditions. Thirdly, the presented method to evaluate the temperature field of the bearing chamber–bearing system has not been studied in other published literature. Additionally, compared with the thermal fluid–structure interaction method, the method described in this paper can save 90.75% of calculation time, which significantly improves efficiency. Therefore, the above method is reliable for evaluating the temperature field of the bearing chamber–bearing system.